Coexistence of thyroglossal duct cyst and second branchial cleft cyst in a young woman: A case report and literature review. (June 2022) - Alarfaj, Abdullah A.
Abstract: Introduction: Thyroglossal cysts represent 70% of congenital neck anomalies, and second branchial cleft anomalies are the most common anomalies (90%) of the branchial apparatus. However, their coexistence, especially in adults, is very rare. Presentation of case: A 23-year-old woman presented with a 1-year history of lateral left neck swelling and midline swelling. Imaging and histopathological examination confirmed the diagnosis of a thyroglossal duct cyst and a second branchial cleft cyst. The Sistrunk procedure was performed for surgical excision of the masses. Discussion: Only three cases of a coexisting thyroglossal duct cyst and branchial cleft have been reported. Conclusion: When encountering patients, even adults, with neck lesions, clinicians must keep in mind the possibility of a coexistence of a thyroglossal duct and a branchial cleft cyst. Highlights: Thyroglossal cysts represent 70% of congenital neck anomalies. Second branchial cleft anomalies are the most common branchial apparatus anomalies. Only three cases of coexisting thyroglossal duct and branchial cleft cysts have been reported. We present a rare case of a young woman with the two cysts coexisting.